| Gaston Tissandier - 1882
...explanations are only wearying and unsatisfactory at best. The principle is, simply stated, the theorem that **the logarithm of the product of two numbers is equal to the sum of** their logs. The size of the dial will of course regulate the length of the calculation. The instrument... | |
| Henry Nathan Wheeler - 1882 - 43 páginas
...3 when the base is 10? Ans. 0.001. § 6. In any system the logarithm of the product of two or more **numbers is equal to the sum of the logarithms of the numbers.** Proof: If l = b", m = by, n = b', then is log6Z = x, Iog6m = 2/, logbn = z; now IX mxn = b* x Ъ»... | |
| Robert Hamilton Pinkerton - 1884 - 176 páginas
...calculated to 7 decimal places. 66. Properties of Logarithms. I. The logarithm of the product of two or more **numbers is equal to the sum of the logarithms of the numbers.** II. The logarithm of a quotient is equal to the logarithm of the dividend diminished by the logarithm... | |
| Charles Davies - 1889 - 320 páginas
...member, we have, a*+y — mrii Whence, from the definition, x + y = Log mn . . . . ( 5.) i That is, **the logarithm of the product of two numbers is equal to the sum of the logarithms of the** tiw numbers. If we divide ( 3 ) by ( 4 ), member by member, wo shall have, m a*-* — -• n Whence,... | |
| William Findlay Shunk - 1890 - 339 páginas
...henee its logarithm lies between 1 and 2, as does the logarithm of 74. 5. The logarithm of the produet **of two numbers is equal to the sum of the logarithms of the numbers.** The logarithm of a quotient is equal to the logarithm of the dividend diminished by that of the divisor.... | |
| John Bascombe Lock - 1892 - 306 páginas
...power of 2 which is equal to 32? The use of Logarithms is based upon the following propositions : — **I, The logarithm of the product of two numbers is equal to the** logarithm of one of the numbers + the logarithm of the other. For, let log. m=x and log,,ra=y, then,... | |
| William Freeland - 1895 - 309 páginas
...is > 1. 393. III. Again, if m" = a, and m' = b, we have m*+' = ab. I fence logab = x + y; that is, **the logarithm of the product of two numbers is equal to the sum of the logarithms of** its factors. 394. IV. Also if m* = a, and m? = b, m*-" = -. Hence, b log - = x — y ; that is, the... | |
| John Bascombe Lock - 1896 - 147 páginas
...8. i ,_ snn о logic 100 = 2. 120. The use of logarithms is based upon the following propositions : **I. The logarithm of the product of two numbers is equal to the** logarithm of one of the numbers plus the logarithm of the other. For, let log, m = x ; then m = b',... | |
| Andrew Wheeler Phillips, Wendell Melville Strong - 1898 - 138 páginas
...of the number m is the number .r which satisfies the equation, ax = 1n. This is written x = loga m. **The logarithm of the product of two numbers is equal to the sum of the logarithms of the numbers.** Thus loga;//я = logaw + logeя. The logarithm of the quotient of two numbers is equal to the logarithm... | |
| University of Sydney - 1904
...respectively equal to a, b and c, prove that — — -^=«. ao 10. Define a logarithm and prove that **the logarithm of the product of two numbers is equal to the sum of** their logarithms. Find the value of = • — . (3-721)"tf Given log 8-4=-9243, log 6'72='8274, log... | |
| |